Investigation of Antimicrobial and Cytotoxic Properties and Specification of Silver Nanoparticles (AgNPs) Derived From Cicer arietinum L. Green Leaf Extract - Baran, Ayşe; Fırat Baran, Mehmet; Keskin, Cumali; Hatipoğlu, Abdulkerim; Yavuz, Ömer; İrtegün Kandemir, Sevgi; Adican, Mehmet Tevfik; Khalilov, Rovshan; Mammadova, Afat; Ahmadian, Elham; Rosić, Gvozden; Selakovic, Dragica; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Using the biological materials to synthesis of metallic nanoparticles has become a frequently preferred method by researchers. This synthesis method is both fast and low cost. In this study, an aqueous extract obtained from chickpea (Cicer arietinum L.) (CA) leaves were used in order to the synthesis silver nanoparticles (AgNPs). For specification of the synthesised AgNPs the UV-vis spectrophotometer, Fourier Transform Infrared Spectroscopy (FT-IR), X-Ray Diffraction Analysis (XRD), Transmission Electron Microscope (TEM), Scanning Electron Microscope (SEM), Electron Dispersive X-rays (EDX) and Zeta potential (ZP) analyses data were used. Biologically synthesized AgNPs demonstrated a maximum surface plasmon resonance of 417.47 nm after 3 hours. With the powder XRD model, the mean crystallite dimensions of nanoparticles were determined as 12.17 mm and cubic structure. According to the TEM results, the dimensions of the obtained silver nanoparticles were found to be 6.11-9.66 nm. The ZP of the the electric charge on the surface of AgNPs was measured as -19.6 mV. The inhibition effect of AgNPs on food pathogen strains and yeast was determined with the minimum inhibition concentration method (MIC). AgNPs demonstrated highly effective inhibition at low concentrations especially against the growth of B. subtilis (0.0625) and S. aureus (0.125) strains. The cytotoxic effects of silver nanoparticles on cancerous cell lines (CaCo-2, U118, Sk-ov-3) and healthy cell lines (HDF) were revealed. Despite the rising of the AgNPs amounts against cancerous and healthy cell lines, no significant decrease in the percentage of viability was detected.